Quaternary copolymer tackifier and its preparation method
By adjusting the molar ratios of acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate, the prepared quaternary copolymers exhibit tackification and high temperature resistance in the medium-permeable oil layer, solving the problem of increased water injection pressure and reduced recovery when used in the medium-permeable oil layer.
Patent Information
- Application Number
- CN202311030663.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2043-08-16
AI Technical Summary
When used in medium permeable oil layers, the water injection pressure increases and the recovery rate decreases. The low molecular weight polymers such as carboxymethylcellulose sodium have poor temperature resistance and cannot meet the needs of high-temperature oil resistance.
Using a tetramer copolymer, by adjusting the molar ratios of acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, sodium acrylate, potassium persulfate and ammonium persulfate are added as initiators, and the reaction is heated under a nitrogen atmosphere, and after freeze-drying, copolymers with tackification and high temperature resistance are obtained.
The prepared tetramers exhibited similar tackification effects to sodium carboxymethylcellulose in medium-permeable reservoirs and had stronger high temperature resistance, which solved the application of existing polymers in medium-permeable oil layers.
Smart Images

Figure QLYQS_1 
Figure BDA0004397151290000021 
Figure BDA0004397151290000022
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical engineering, and particularly relates to a tetrapolymer tackifier and a preparation method thereof. Background Art
[0002] Polyacrylamide is a linear, water-soluble polymer flooding agent widely used in oilfields. Its function is to adjust the rheological properties of injected water, increase the viscosity of the drive fluid, improve water flooding sweep efficiency, and enable water and oil to flow forward at a uniform rate. However, the molecular weight of currently used polyacrylamide polymer flooding agents is generally relatively large (tens of millions), resulting in increased injection pressure and reduced recovery when used in medium-permeability reservoirs, resulting in poor development results.
[0003] When injecting polymers into medium-permeability reservoirs, lower molecular weight polymers are easier to inject. However, low molecular weight polyacrylamide solutions also have low viscosity. Sodium carboxymethyl cellulose, a low molecular weight polymer with good viscosity-increasing properties, suffers from poor temperature resistance and cannot meet the demand for high-temperature resistant polymers for oil recovery. Therefore, the key technology needed to develop a new low molecular weight polymer flooding agent with good viscosity-increasing properties and high temperature resistance, which can easily penetrate medium-permeability reservoirs, is urgently needed. Summary of the Invention
[0004] One of the purposes of the present invention is to provide a tetrapolymer tackifier having a similar tackifying effect to sodium carboxymethyl cellulose and stronger high temperature resistance.
[0005] To achieve the above object, the present invention adopts the following technical solution: a tetrapolymer, the general structural formula of which is shown in formula (I).
[0006]
[0007] Among them, y:w:x:z=4~14:1~6:1:0.2~5, n=9.
[0008] The preparation reaction formula of the compound of formula I is shown below:
[0009]
[0010] The preparation method of the compound of formula I is as follows: acrylamide, N-isopropyl methacrylamide, methoxy polyethylene glycol acrylate, and sodium acrylate are added to ultrapure water and stirred to dissolve, potassium persulfate and ammonium persulfate are added and stirred to dissolve, then the above solution is purged with nitrogen for 30 minutes to expel the air in the reaction system, and then the reaction solution is heated to 70°C under a nitrogen atmosphere and stirred for reaction. After the reaction is completed, the reaction solution is cooled to room temperature and then added to a dialysis bag, dialyzed with ultrapure water for 3 days, and freeze-dried to obtain a tetrapolymer.
[0011] Among them, the molar ratio of acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the feed is 8-24:4-8:2:0.5-8, preferably 24:4:2:6;
[0012] The molecular weight of methoxypolyethylene glycol acrylate is 480 Da;
[0013] The total amount of potassium persulfate and ammonium persulfate is 0.08-0.2% of the total mass of the four polymerization monomers, and the mass ratio of potassium persulfate to ammonium persulfate is 2:1;
[0014] The stirring reaction time is 2-24 hours.
[0015] The advantages of the present invention are as follows: By adjusting the feeding ratio of the four polymerization monomers, a quaternary copolymer with different polymerization unit compositions can be prepared. By changing the molar ratio of the four polymerization units in the copolymer, a quaternary copolymer thickener with a similar thickening effect and stronger high-temperature resistance to sodium carboxymethylcellulose can be obtained. Brief Description of the Drawings
[0016] Figure 1 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 1 of the present invention in deuterated water.
[0017] Figure 2 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 2 of the present invention in deuterated water.
[0018] Figure 3 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 3 of the present invention in deuterated water.
[0019] Figure 4 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 4 of the present invention in deuterated water.
[0020] Figure 5 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 5 of the present invention in deuterated water.
[0021] Figure 6 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 6 of the present invention in deuterated water.
[0022] Figure 7 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 7 of the present invention in deuterated water.
[0023] Figure 8 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 9 of the present invention in deuterated water.
[0024] Figure 9 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 10 of the present invention in deuterated water.
[0025] Figure 10 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Example 11 of the present invention in deuterated water.
[0026] Figure 11 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate) prepared in Comparative Example 3 of the present invention in deuterated water.
[0027] Figure 12 1H NMR spectrum of poly(acrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) prepared in Comparative Example 6 of the present invention in deuterated water.
[0028] Figure 13 1H NMR spectrum of poly(acrylamide-N-isopropylmethacrylamide-sodium acrylate) prepared in Comparative Example 7 of the present invention in deuterated water. Detailed implementation mode
[0029] The present invention will be further described below in conjunction with specific embodiments;
[0030] Preparation of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate-sodium acrylate).
[0031] Example 1
[0032] 1.42 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 0.118 g of sodium acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 24 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (with a molecular weight cut-off of 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0033] The prepared copolymer was characterized by 1H NMR spectroscopy, as shown in Figure 1 . By the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shifts 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 4.24:2.21:1:0.27. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 182673, and the polydispersity index was 1.7.
[0034] Example 2
[0035] 1.42 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 0.235 g of sodium acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 24 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (with a molecular weight cut-off of 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0036] The prepared copolymer was characterized by 1H NMR spectroscopy, as shown in Figure 2 . By the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shifts 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 4.14:2.07:1:0.52. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 179693, and the polydispersity index was 1.55.
[0037] Example 3
[0038] 1.42 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 0.47 g of sodium acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added, stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 24 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0039] The prepared copolymer was characterized by 1H NMR, as shown in Figure 3 . Through the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shift 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 4.82:2.26:1:0.96. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 175781, and the polydispersity index was 1.73.
[0040] Example 4
[0041] 2.13 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 0.71 g of sodium acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added, stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 24 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0042] The prepared copolymer was characterized by 1H NMR, as shown in Figure 4 . Through the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shift 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 9.37:2.38:1:1.86. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 187286, and the polydispersity index was 1.69.
[0043] Example 5
[0044] 2.84 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 0.94 g of sodium acrylate were added to 80 mL of ultrapure water and dissolved by stirring at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and dissolved by stirring at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 24 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0045] The prepared copolymer was characterized by 1H NMR, as shown in Figure 5 . Through the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shift 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 10.09:2.07:1:2.05. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 192478, and the polydispersity index was 1.56.
[0046] Example 6
[0047] 4.26 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 1.18 g of sodium acrylate were added to 80 mL of ultrapure water and dissolved by stirring at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and dissolved by stirring at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 2 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0048] The prepared copolymer was characterized by 1H NMR, as shown in Figure 6 . Through the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shift 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 12.1:1.89:1:2.55. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 201823, and the polydispersity index was 1.66.
[0049] Example 7
[0050] 4.26 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 1.41 g of sodium acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 2 hours. Then the reaction solution was cooled to room temperature and dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0051] The prepared copolymer was characterized by 1H-NMR, as shown in Figure 7 . Through the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shift 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 13.3:2.62:1:2.84. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 215267, and the polydispersity index was 1.59.
[0052] Example 8
[0053] 4.97 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 1.65 g of sodium acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred. Gelation occurred after 2 hours of reaction.
[0054] Example 9
[0055] 4.26 g of acrylamide, 2.54 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 1.41 g of sodium acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 2 hours. Then the reaction solution was cooled to room temperature and dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0056] The prepared copolymer was characterized by 1H-NMR, as shown in Figure 8。The molar ratio of acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 12.93:4.76:1:2.72 based on the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signals of the polymer backbone (chemical shifts 1.6 and 2.1), as well as the results of elemental analysis. The number-average molecular weight of the copolymer was measured to be 227,635 by gel permeation chromatography, and the polydispersity index was 1.72.
[0057] Example 10
[0058] 4.26 g of acrylamide, 2.54 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 1.88 g of sodium acrylate were added to 80 mL of ultrapure water and stirred to dissolve at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred to dissolve at room temperature. Nitrogen was introduced to expel air for 30 minutes, and the reaction solution was heated to 70 °C and stirred for 24 hours under nitrogen protection. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0059] The prepared copolymer was characterized by nuclear magnetic resonance hydrogen spectroscopy, as shown in Figure 9 。The molar ratio of acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 13.85:5.49:1:4.07 based on the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signals of the polymer backbone (chemical shifts 1.6 and 2.1), as well as the results of elemental analysis. The number-average molecular weight of the copolymer was measured to be 218,273 by gel permeation chromatography, and the polydispersity index was 1.68.
[0060] Example 11
[0061] 4.26 g of acrylamide, 2.54 g of N-isopropylmethacrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 0.47 g of sodium acrylate were added to 80 mL of ultrapure water and stirred to dissolve at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred to dissolve at room temperature. Nitrogen was introduced to expel air for 30 minutes, and the reaction solution was heated to 70 °C and stirred for 2 hours under nitrogen protection. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (cut-off molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0062] The prepared copolymer was characterized by nuclear magnetic resonance hydrogen spectroscopy, as shown inFigure 10 By the integral ratio of the methyl hydrogen signal of N-isopropyl methacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer main chain (chemical shift 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropyl methacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 12.23:4.04:1:1.02. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 235643, and the polydispersity index was 1.67.
[0063] Example 12
[0064] 4.26 g of acrylamide, 1.27 g of N-isopropyl methacrylamide, 4.8 g of methoxypolyethylene glycol acrylate, and 1.41 g of sodium acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added, stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred. Gelation occurred after 2 hours of reaction.
[0065] Preparation of poly(acrylamide-N-isopropyl methacrylamide-methoxypolyethylene glycol acrylate) in Comparative Example 1
[0066] 4.26 g of acrylamide, 1.27 g of N-isopropyl methacrylamide, and 2.4 g of methoxypolyethylene glycol acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added, stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred. Gelation occurred after 2 hours of reaction.
[0067] Preparation of poly(acrylamide-N-isopropyl methacrylamide-methoxypolyethylene glycol acrylate) in Comparative Example 2
[0068] 4.26 g of acrylamide, 2.54 g of N-isopropyl methacrylamide, and 2.4 g of methoxypolyethylene glycol acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added, stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred. Gelation occurred after 2 hours of reaction.
[0069] Preparation of poly(acrylamide-N-isopropyl methacrylamide-methoxypolyethylene glycol acrylate) in Comparative Example 3
[0070] 4.26 g of acrylamide, 3.81 g of N-isopropylmethacrylamide, and 2.4 g of methoxypolyethylene glycol acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was passed through to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 5 hours. Then, the reaction solution was cooled to room temperature and dialyzed (cut-off molecular weight 3500 Da) in ultrapure water for 3 days, followed by freeze-drying to obtain a white solid.
[0071] The prepared copolymer was characterized by 1H-NMR, as shown in Figure 11 . Based on the integral ratios of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0), the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4), and the hydrogen signal of the polymer backbone (chemical shifts 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, and methoxypolyethylene glycol acrylate in the copolymer was calculated to be 13.7:6.52:1. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 214397, and the polydispersity index was 1.75.
[0072] Preparation of poly(acrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) in Comparative Example 4
[0073] 4.26 g of acrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 1.41 g of sodium acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was passed through to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred. Gelation occurred after 1 hour of reaction.
[0074] Preparation of poly(acrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) in Comparative Example 5
[0075] 4.26 g of acrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 1.88 g of sodium acrylate were added to 80 mL of ultrapure water and stirred at room temperature until dissolved. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred at room temperature until dissolved. Nitrogen was passed through to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred. Gelation occurred after 2 hours of reaction.
[0076] Preparation of poly(acrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) in Comparative Example 6
[0077] 4.26 g of acrylamide, 2.4 g of methoxypolyethylene glycol acrylate, and 2.35 g of sodium acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 2 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (retention molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0078] The prepared copolymer was characterized by 1H NMR, as shown in Figure 12 . Through the integral ratio of the polyethylene glycol signal of methoxypolyethylene glycol acrylate (chemical shift 3.4 - 4.4) and the hydrogen signal of the polymer backbone (chemical shifts 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate in the copolymer was calculated to be 17.9:1:7.46. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 183524, and the polydispersity index was 1.64.
[0079] Preparation of poly(acrylamide-N-isopropylmethacrylamide-sodium acrylate) in Comparative Example 7
[0080] 4.26 g of acrylamide, 1.27 g of N-isopropylmethacrylamide, and 1.41 g of sodium acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred for 24 hours. Then the reaction solution was cooled to room temperature, dialyzed in ultrapure water (retention molecular weight 3500 Da) for 3 days, and freeze-dried to obtain a white solid.
[0081] The prepared copolymer was characterized by 1H NMR, as shown in Figure 13 . Through the integral ratio of the methyl hydrogen signal of N-isopropylmethacrylamide (chemical shift 1.0) and the hydrogen signal of the polymer backbone (chemical shifts 1.6 and 2.1), as well as the results of elemental analysis, the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, and sodium acrylate in the copolymer was calculated to be 13.19:2:2.86. The number-average molecular weight of the copolymer measured by gel permeation chromatography was 198273, and the polydispersity index was 1.73.
[0082] Preparation of poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate) in Comparative Example 8
[0083] 1.42 g of acrylamide, 1.27 g of N - isopropylmethacrylamide, and 2.4 g of methoxypolyethylene glycol acrylate were added to 80 mL of ultrapure water, stirred and dissolved at room temperature. 6 mg of potassium persulfate and 3 mg of ammonium persulfate were added and stirred and dissolved at room temperature. Nitrogen was introduced to expel air for 30 minutes. Under nitrogen protection, the reaction solution was heated to 70 °C and stirred. Gelation occurred after 2 hours of reaction.
[0084] Example 13 Viscosity Detection of 2% and 1% Aqueous Copolymer Solutions
[0085] Preparation of 2% aqueous copolymer solution: The copolymers prepared in Examples 1, 2, 3, 4, 5, 6, 7, 9, 10, 11, Comparative Examples 3, 6, and 7 were added to ultrapure water, stirred and dissolved at room temperature to prepare aqueous copolymer solutions with mass concentrations of 1% and 2% respectively.
[0086] Viscosity detection: The viscosities of the above - prepared 2% aqueous copolymer solutions at different temperature conditions were measured by a digital rotational viscometer with a shear rate of 100 s -1 .
[0087] In Comparative Example 8, when acrylamide, N - isopropylmethacrylamide, and methoxypolyethylene glycol acrylate were fed and reacted in a molar ratio of 4:2:1, gelation occurred after 2 hours of reaction. To prevent gelation, based on the polymerization monomers acrylamide, N - isopropylmethacrylamide, and methoxypolyethylene glycol acrylate, sodium acrylate was introduced to polymerize a quaternary copolymer, and the gelation process was prevented by the electrostatic repulsion of sodium acrylate.
[0088] Table 1 Viscosity (mPa·s) of 2% Aqueous Copolymer Solutions vs. Temperature
[0089]
[0090] Table 2 Viscosity (mPa·s) of 1% Aqueous Copolymer Solutions vs. Temperature
[0091]
[0092] Table 1 shows the values of viscosity varying with temperature when the concentration of each copolymer is 2%. By comparing Examples 1, 2, and 3, it can be seen that when acrylamide, N-isopropylmethacrylamide, and methoxypolyethylene glycol acrylate are fed in a molar ratio of 4:2:1, and sodium acrylate is introduced for polymerization, gelation can be prevented. The viscosity of the aqueous solution of the quaternary copolymer prepared increases with the increase of the molar ratio of the sodium acrylate unit. This is because the sodium acrylate unit carries a negative charge, which can cause the polymer chains to stretch through electrostatic repulsion, increasing the volume of the polymer coils and thus increasing the viscosity. When the molar ratio of the sodium acrylate unit is increased from 0.52 (Example 2) to 0.96 (Example 3), the increase in the viscosity of the aqueous solution of the quaternary copolymer is limited.
[0093] By comparing Examples 3, 4, 5, 6, and 7, it can be seen that on the basis of Example 3, while keeping the feeding ratio of N-isopropylmethacrylamide and methoxypolyethylene glycol acrylate unchanged, and increasing the feeding ratios of acrylamide and sodium acrylate simultaneously, the viscosity of the aqueous solution of the quaternary copolymer can be continuously increased. This is because acrylamide can provide hydrogen bond interactions, increasing the association between polymer chains, and sodium acrylate can enhance the electrostatic repulsion effect, causing the polymer chains to stretch. Among them, the viscosity of the aqueous solution of the quaternary copolymer prepared in Example 7 is the largest (the molar ratio of the polymerization units acrylamide, N-isopropylmethacrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate is 13.3:2.62:1:2.84). Further increasing the feeding ratios of acrylamide and sodium acrylate on the basis of Example 7 will lead to gelation, as shown in Example 8.
[0094] By comparing Examples 7, 9, 10, and 11, it can be seen that on the basis of Example 7, increasing the feeding ratio of N-isopropylmethacrylamide will result in a decrease in the viscosity of the aqueous solution of the quaternary copolymer, mainly because the increase in the molar ratio of the N-isopropylmethacrylamide unit will affect the association between polymer chains through hydrogen bond interactions due to steric hindrance effects. On the basis of Example 7, increasing the feeding ratio of methoxypolyethylene glycol acrylate will lead to gelation, as shown in Example 12. This is because the increase in the molar ratio of the methoxypolyethylene glycol acrylate unit causes the entanglement of polyethylene glycol chains and hydrogen bond interactions to alternate, resulting in strong irreversible association between polymer molecules.
[0095] Based on Example 7, polymerization was carried out using only acrylamide, N-isopropylmethacrylamide, and methoxypolyethylene glycol acrylate to prepare the terpolymer poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate), which led to gelation. See Comparative Example 1. Gelation was prevented by increasing the feed ratio of N-isopropylmethacrylamide (Comparative Examples 2 and 3). A non-gelling poly(acrylamide-N-isopropylmethacrylamide-methoxypolyethylene glycol acrylate) was obtained only when the molar ratio of N-isopropylmethacrylamide units increased to 6.52 (Comparative Example 3).
[0096] Based on Example 7, polymerization was carried out using only acrylamide, methoxypolyethylene glycol acrylate, and sodium acrylate to prepare the terpolymer poly(acrylamide-methoxypolyethylene glycol acrylate-sodium acrylate), which led to gelation. See Comparative Example 4. Gelation was prevented by increasing the feed ratio of sodium acrylate (Comparative Examples 5 and 6). A non-gelling poly(acrylamide-methoxypolyethylene glycol acrylate-sodium acrylate) was obtained only when the molar ratio of sodium acrylate units increased to 7.46 (Comparative Example 6). Based on Example 7, polymerization was carried out using only acrylamide, N-isopropylmethacrylamide, and sodium acrylate, and the terpolymer poly(acrylamide-N-isopropylmethacrylamide-sodium acrylate) was successfully prepared. See Comparative Example 7.
[0097] Comparing Example 7 with Comparative Examples 3, 6, and 7, it can be seen that the quaternary copolymer prepared in Example 7 has better thickening effect than the terpolymers prepared in Comparative Examples 3, 6, and 7. The viscosities of the aqueous solutions of all the prepared copolymers decrease with increasing temperature.
[0098] Table 2 shows the values of viscosity change with temperature when the concentration of each copolymer is 1%. Comparing Table 2 and Table 1, it can be seen that the viscosity of each copolymer changes significantly with concentration, and the higher the concentration, the greater the viscosity.
[0099] Viscosity detection of 2% and 1% polymer aqueous solutions in Example 14
[0100] Preparation of 2% and 1% polymer aqueous solutions: The copolymer prepared in Example 7 and sodium carboxymethylcellulose were respectively added to ultrapure water and stirred at room temperature for dissolution to prepare the polymer aqueous solutions with mass concentrations of 2% and 1%.
[0101] Viscosity detection: The viscosities of the above-prepared 2% and 1% polymer aqueous solutions under different temperature conditions were measured by a digital rotational viscometer at a shear rate of 100 s -1 . The viscosity at 20°C of each polymer aqueous solution was taken as 100%, and the percentage of the viscosity of each polymer aqueous solution under different temperature conditions was calculated.
[0102] To compare the thickening effect and high temperature resistance of the quaternary copolymer prepared in Example 7 with those of sodium carboxymethyl cellulose, the quaternary copolymer prepared in Example 7 and sodium carboxymethyl cellulose were configured into aqueous solutions with mass fractions of 2% and 1%, and the temperature was raised to 80 °C to measure the change in viscosity with temperature. As shown in Table 3, when the concentration of the aqueous solution of the quaternary copolymer prepared in Example 7 was 1%, the viscosity at 20 °C was 104.6 mPa·s, and when the concentration was 2%, the viscosity at 20 °C was 208.4 mPa·s. The viscosity of the aqueous solution of sodium carboxymethyl cellulose at a concentration of 1% was 110.4 mPa·s at 20 °C, and at a concentration of 2%, the viscosity at 20 °C was 215.5 mPa·s, indicating that the quaternary copolymer prepared in Example 7 and sodium carboxymethyl cellulose have similar thickening effects at room temperature. As shown in Tables 4 and 5, the viscosities of the aqueous solutions of the quaternary copolymer prepared in Example 7 and sodium carboxymethyl cellulose both decreased with the increase in temperature. Comparatively, the decrease in the viscosity of the aqueous solution of the quaternary copolymer prepared in Example 7 was smaller than that of the aqueous solution of sodium carboxymethyl cellulose, indicating that the quaternary copolymer prepared in Example 7 has better high temperature resistance than sodium carboxymethyl cellulose.
[0103] Table 3. Viscosities (mPa·s) of 1% and 2% aqueous solutions of Example 7 and sodium carboxymethyl cellulose
[0104] Temperature / °C 2% Example 7 2% Sodium carboxymethylcellulose 1% Example 7 1% Sodium carboxymethylcellulose 20 208.4 215.5 104.6 110.4
[0105] Table 4. Variation of viscosity percentage of 2% polymer aqueous solution with temperature
[0106] Temperature / °C Example 7 Sodium carboxymethylcellulose 20 100.0% 100.0% 30 93.4% 93.1% 40 87.2% 83.0% 50 76.3% 68.8% 60 63.3% 59.2% 70 55.2% 44.9% 80 48.0% 37.1%
[0107] Table 5. Variation of viscosity percentage of 1% polymer aqueous solution with temperature
[0108] Temperature / °C Example 7 Sodium carboxymethylcellulose 20 100.0% 100.0% 30 93.5% 92.9% 40 86.4% 82.7% 50 75.2% 68.3% 60 62.8% 58.7% 70 54.6% 44.5% 80 47.6% 36.6% 。
Claims
1. A tetrapolymer tackifier, characterized in that: The general structural formula of the tetrapolymer is shown in formula (I): , Ⅰ Among them, y:w:x:z=4~14:1~6:1:0.2~5, n=9; The preparation method of the tetrapolymer comprises: adding acrylamide, N-isopropyl methacrylamide, methoxy polyethylene glycol acrylate, and sodium acrylate to ultrapure water, stirring and dissolving them, adding potassium persulfate and ammonium persulfate, stirring and dissolving them, then passing nitrogen through the solution for 30 minutes to expel air from the reaction system, heating the reaction solution to 70° C. under a nitrogen atmosphere, stirring and reacting, cooling the reaction solution to room temperature after the reaction is completed, then adding the reaction solution to a dialysis bag, dialyzing it with ultrapure water for 3 days, and freeze-drying it to obtain the tetrapolymer; The molar ratio of acrylamide, N-isopropyl methacrylamide, methoxy polyethylene glycol acrylate, and sodium acrylate is 8-24:4-8:2:0.5-8; The total amount of potassium persulfate and ammonium persulfate is 0.08-0.2% of the total mass of the four polymer monomers, and the mass ratio of potassium persulfate to ammonium persulfate is 2:
1.
2. The tetrapolymer tackifier according to claim 1, characterized in that The molecular weight of methoxy polyethylene glycol acrylate is 480 Da.
3. The tetrapolymer tackifier according to claim 1, characterized in that The reaction time is 2 to 24 hours.
Citation Information
Patent Citations
High-temperature-resistant thickening agent for fracturing fluid, and preparation method and application thereof
CN111019042A
Reverse temperature-sensitive gel fracturing fluid thickening agent and preparation method thereof
CN113429528A